Relações hídricas e trocas gasosas em plantas de feijão submetidas à irrigação deficitária - François, Ticiana (2012)
The constant deficiency of available water resources and the society pressure for the rational water use in agriculture requires the correct management of the irrigation water. When a plant does not receive the right amount of water, it will affect the crop yield. The deficit irrigation contributes to increase the crops yield, comparing to a systems without irrigation, and as a results the agriculture will be more efficient preserving the quality ant quantity of natural recourses increasing or maintaining the crop yield. Therefore, this study is justified insofar as it seeks to identify deficit irrigation management in order to maintain satisfactory productivity, coupled with the water savings. The objective of this research was to evaluate water relations and gas exchange through the assessment of physiological variables that indicate changes in the crop yield of dry bean submitted to deficit irrigation. The experiment was conducted at the Federal University of Santa Maria, Brazil, under a mobile greenhouse, which was only closed during the occurrence of rain. In this way, there was no rainfall interference affecting the treatments. A completely randomized design was used with three replications. Treatments were consisted of four irrigation managements: 100% of accumulated crop evapotranspiration (ETc ac), and deficit irrigation of 75%, 50% and 25% of the ETc ac. Dry beans was sowed under a no tillage system, and the irrigation need was determined based on crop evapotranspiration values estimated using Penman-Monteith method, and the crop coefficients (Kc) used were those proposed by Allen et al. (1998). Irrigations were applied when the ETc accumulated a height of 20mm. The following leaf water relations and leaf gas exchanges were evaluated: Transpiration rate, stomatal conductance, leaf steam pressure deficit, internal concentration of CO2 and photosynthesis rate, using a LI-6400 (LI-Cor). With the values of photosynthesis rate, transpiration rate, stomatal conductance and internal concentration of CO2 were determined: transpiration instantaneous efficiency (photosynthesis rate/transpiration rate); intrinsic water use efficiency and (photosynthesis rate/stomatal conductance); carboxylation efficiency of the plants (photosynthesis rate/internal concentration of CO2). The following morphological features were evaluated: leaf area index, plant height and yield compounds (one hundred mass grains, number of seed plant and crop yield). The water use efficiency (EUA) was found by the ratio between grain yield (kg ha-1) and total depth applied (mm). During crop development accumulated ETc was 379,7 mm and was applied 122, 206, 290 and 376 mm of irrigation depth for the deficit irrigation treatment of 25%, 50%, 75% and 100% of ETc ac, respectively. The application of deficit irrigation reduced the leaf area index, plant height and reduction of 47,41% in the number of seed plant, 39,26%, in one hundred mass grain and 53,41% in crop yield. The reduction in water depth from 100% to 25% of ETc ac reduced by up to 91% of the stomatal concuctance and these plants had lower photosynthesis rate. The plants that received irrigation depth of 100% of ETc ac had higher E and carboxylation efficiency. The intrinsic water use efficiency and water use efficiency increased with the use of deficit irrigation.